Kisah Dakwah Nabi Shaleh Perspektif Strukturalisme Naratologi Aj Greimas: Kajian Semiotika Terhadap Qs. As-Syu’ara: 141-158 - Reza, Ainullah (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2018)
This article examines the story of the Prophet Shaleh’s dakwah to the Thamud recorded in the QS. as-Syu'ara: 141-158 in semiotic perspective. The theory of AJ Greimas' naraotogical structuralism is used to identify the discourses inherent in the story. it also explains the narrative structure of the story in order to trace the values and ideologies contained by analyzing the actal schemes and their functional structures. The propagation story of the Prophet (pbuh) to the Thamud actually tells a very 'humanistic' problem, a heart that tends to be inconsistent to the truth because of the intervening materialistic tendencies. The solution offered in the story avoids the possibility of materialistic intervention and dedicates itself to the good. Whether it's a vertical goodness (to God) or a horizontal (to fellow creatures). Through Greimas's semiotics perspective, the story not only attempts to convey the meaning of obedience or piety and the disobedience of a righteous thing, but also emphasizes the moral dimension and credibility of human. The words of the Holy Prophet Shaleh in verse 153 lead to the value of environmentalist, the attitude of preserving and preserving the environment. In addition, the story leads to a psychological dimension, that the person who dedicates himself to the goodness tends to be anti-materialistic. It is seen in the self of the Holy Prophet Shaleh who does not expect anything at all except the obedience of the Thamud.